Functions of estrogen and estrogen receptor signaling on skeletal muscle. Issue 191 (July 2019) - Ikeda, Kazuhiro; Horie-Inoue, Kuniko; Inoue, Satoshi
Highlights: Estrogen plays a crucial role in skeletal muscle homeostasis and exercise capacity. Estrogen decrease may associate with sarcopenia and frailty in postmenopausal women. Estrogen maintains mitochondrial function and metabolism in female muscle. Estrogen improves exercise endurance and mitochondrial energy metabolism in mice. Understanding of estrogen function in skeletal muscle is useful for healthy life. Abstract: Activity of estrogen, a sex steroid hormone, is not only limited to the reproductive organs but also involves other organs and tissues, including skeletal muscle. In postmenopausal women, estrogen decline causes endocrine and metabolic dysfunction, leading to a predisposition to osteoporosis, metabolic syndrome, and decreased muscle mass and strength. The decline in skeletal muscle mass often associates with sarcopenia, a popular condition observed in fragile elder people. In addition, varying estrogen levels associated with the menstrual phases may modulate exercise performance in women. Estrogen is thus considered to play a crucial role in skeletal muscle homeostasis and exercise capacity, although its precise mechanisms remain to be elucidated. In this article, we review the role of estrogen in the skeletal muscle, outlining the proposed molecular mechanisms. We especially focus on the current understanding of estrogen actions on mitochondria metabolism in skeletal muscle.